ASPERGILLUS FLAVUS INFECTION AND AFLATOXIN CONTAMINATION IN PEANUTS AT VARIOUS STAGES OF THE DELIVERY CHAINS IN WONOGIRI REGENCY, CENTRAL JAVA, INDONESIA - Okky Setyawati Dharmaputra; Ina Retnowati; Santi Ambarwati (Biotropia: The Southeast Asian Journal of Tropical Biology, 2008)
As a part of an Australian Centre for International Agricultural Research (ACIAR) project on management of aflatoxin in Indonesia and Australia (PHT 97/017), a survey on pre- and postharvest handling of peanuts at farmer, collector retailer levels, including Aspergillus flavus Â infection and aflatoxin B1 contamination of peanuts collected in Wonogiri regency, Central Java, was conducted during the harvest period of the wet (February 2003) and dry (June 2003) seasons. Interviews using questionnaires, with farmers, collectors and retailers concerning pre- and post-harvest handling of peanuts were carried out. The moisture contents and physical quality of the peanut kernels were also determined.